Elements of Mission Theology in Ukrainian Orthodox Discourse - Havryliuk, Tetiana (Occasional papers on religion in Eastern Europe, 2024)
The article analyzes the trends in the development of ideas of mission theology in modern Ukrainian Orthodox theology. It was noted that the ideas of mission theology have significant potential in building a new theological discourse that will effectively overcome the crisis of Ukrainian Orthodoxy. It is shown that considering the special modern socio-political situation in which the Church lives and works, Orthodox theology acquired certain Ukrainian features. It deepens the ideas of the theology of communication and Love; there is a turn to communication with the modern world; the need to involve every Orthodox person in the mission of the holy apostles deepens; a new type of Orthodox worldview is being formed, the characteristic features of which should be free-thinking, dignity, freedom; focuses on social service in the conditions of war; the idea of reconciliation is actively developing as the main mission of the Church. The development of the ideas of the theology of the mission is also observed in the theology of Metropolitan Epiphanius. A characteristic feature of the development of the ideas of mission theology by Ukrainian Orthodox theologians is the deepening of its anthropological component rather than triadology, which indicates the relevance of theology to the challenges that Ukrainian Orthodoxy faces today.